Guide to the English school in international studies - Navari, Cornelia, 1941- (Chichester, West Sussex : Wiley Blackwell, 2014)
'Serves as an essential reference for students, researchers, and academics in international relations'--
Includes bibliographical references and index.
Keywords: International relations -- Philosophy; International relations -- United Kingdom